Análise da lubricidade do biodiesel brasileiro de ésteres etílicos de soja e girassol - Farias, Aline Cristina Mendes de (2011)
Fuel is a material used to produce heat or power by burning, and lubricity is the capacity for reducing friction. The aim of this work is evaluate the lubricity of eight fossil and renewable fuels used in Diesel engines, by means of a HFRR tester, following the ASTM D 6079-04 Standard. In this conception, a sphere of AISI 52100 steel (diameter of 6,000,05 mm, Ra 0,050,005 μm, E = 210 GPa, HRC 624, HV0,2 63147) is submitted to a reciprocating motion under a normal load of 2 N and 50 Hz frequency to promote a wear track length of 1.10.1mm in a plan disc of AISI 52100 steel (HV0,05 18410, Ra 0,020,005 μm). The testing extent time was 75 minutes, 225,000 cycles. Each one test was repeated six times to furnish the results, by means of intrinsic signatures from the signals of the lubricant film percentage, friction coefficient, contact heating, Sound Pressure Level, SPL [dB]. These signal signatures were obtained by two thermocouples and a portable decibelmeter coupled to a data acquisition system and to the HFRR system. The wettability of droplet of the diesel fuel in thermal equilibrium on a horizontal surface of a virgin plan disc of 52100 steel, Ra 0,02  0,005 μm, were measured by its contact angle of 7,0  3,5o, while the results obtained for the biodiesel B5, B20 and B100 blends originated by the ethylic transesterification of soybean oil were, respectively, 7,5  3,5o, 13,5  3,5o e 19,0  1,0o; for the distilled water, 78,0  6,0o; the biodiesel B5, B20 and B100 blends originated by the ethylic transesterification of sunflower oil were, respectively, 7,0  4,0o, 8,5  4,5o e 19,5  2,5o. Different thickness of lubricant film were formed and measured by their percentage by means of the contact resistance technique, suggesting several regimes, since the boundary until the hydrodynamic lubrication. All oils analyzed in this study promoted the ball wear scars with diameters smaller than 400 μm. The lowest values were observed in the scar balls lubricated by mixtures B100, B20 and B5 of sunflower and B20 and B5 of soybean oils (WSD < 215 μm)